Parâmetros seminais e proteoma do plasma seminal de carneiros morada nova submetidos a insulação escrotal intermitente - Viana Neto, Aderson Martins (2018)
The study evaluated the changes in testicular biometry, seminal parameters, DNA integrity, localization of RSVP-sperm interaction and seminal plasma proteome (2D-SDS-PAGE) of rams submitted to intermittent scrotal insulation. Six adult Morada Nova rams have had their testis insulated by four nights (6:00 p.m. a 6:00 a.m.), a total of 48 hours. Semen was collect by eletroejaculation from 14 days before until 120 days after begin of scrotal insulation. Scrotal circumference decreased from 30.5 ± 0,34 cm (day 0) to 27.9 ± 0,58 cm (day 28) and it was recovered to normal at day 57 (30.6 ± 0,62 cm). Total motility declined from 75% (day 0) to 33% (day 4) being absent at day 23 and 28, and it was reestablished at day 77 (67%). The percentage of normal sperm was reduced from 96% (day 0) to 6% (day 7) being recovered at day 91 (87%). Sperm DNA integrity was smallest values during day 11 to 63, returning to normal 120 days after begin of scrotal insulation (80,4%). The percentage of immunolocalizated-RSVP sperm decreased 20% after intermittent scrotal insulation (pre-insulation: 54.9%; post-insulation: 34,6%). It were detected 342 spots in master gel, so that 13 spots diffentially expressed corresponded to 14 proteins, of which, nine was underexpressed (Carboxypeptidase Q precursor, Beta-actin-like protein 2, Superoxide dismutase [CuZn], Mammaglobin A, Spermadhezin z-13, Epididymal secretory protein E1, Binder of sperm 5 precursor, Aldose reductase, Creactive protein), while others five was overexpressed (Serum albumin precursor, Inhibitor of carbonic anhydraselike, Inactive ribonuclease-like protein 9, EGF-like repeat and discoidin I-like domain-containing protein 3 e Polymeric immunoglobulin receptor) after intermittent scrotal insulation. Therefore, scrotal hyperthermia results in microscopy and molecular changes that reduces seminal quality in rams raised at tropical climate.